Implementing the Five Rs of Nutrient Stewardship for Fertigation in Florida’s Vegetable Production - Mary Dixon; Guodong Liu (EDIS)
The five Rs of nutrient stewardship is a mnemonic device used to emphasize accuracy and precision for nutrient management so as to apply the (1) right source of fertilizer at the (2) right rate at the (3) right time in the (4) right place with the (5) right irrigation. Because the majority of Florida's soils are sandy, this fifth R is imperative for sustainable nutrient management for commercial crop production. These main points of nutrient management (source, rate, time, place, irrigation) may help enhance sustainability by reducing pollution by eutrophication, nitrogen loss through ammonia volatilization, and climate change from soil greenhouse gas emission. This new 8-page publication of the UF/IFAS Horticultural Sciences Department was written by Mary Dixon and Guodong Liu. https://edis.ifas.ufl.edu/hs1386